Creating casual games for profit & fun - Partridge, Allen (Charles River Media, 2007)
Thousands of game enthusiasts and would-be developers are searching habitually for an opportunity to expand their knowledge of games. Whether they're clicking through Amazon or browsing Barnes and Noble, they are all looking for a path to their dream, a secret door into the games industry. The Casual Games Market is that secret passage. The industry, featuring online downloadable games generally delivered through distributors like Real-One Arcade, Shockwave.com and Oberon Media (via MSN Games and Pogo) has exploded over the past five years into a multi-billion dollar annual marketplace. Independent developers have rapidly discovered the field as one of the last remaining venues to break into the public eye